2018
DOI: 10.1021/acs.organomet.8b00223
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and Diplatinum Polyynediyl Complexes as Potential Push–Pull Chromophores: Synthesis, Characterization, TD-DFT Modeling, and Photophysical and NLO Properties

Abstract: This paper presents the syntheses, the photophysical and the electrochemical characterizations of four new mono-and diplatinum polyynediyl complex chromophores end-capped with diphenylpyranylidene and pentafluorophenyl moieties. The nonlinear optical properties (NLO) of these compounds is investigated using the Electric-Field-Induced Second Harmonic generation (EFISH) technique and their experimental optical properties are confirmed by Time-Dependent Density Functional Theory (TD-DFT) with a range-separated hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“… 60 62 For explaining the structure–property of a molecule concerning the NLO characters, the concepts of polarizability and hyperpolarizability are helpful. 63 In addition to the NLO response, the properties of organic compounds offer a crucial role in the internal charge-transfer process and extended π-conjugated systems. 64 …”
Section: Resultsmentioning
confidence: 99%
“… 60 62 For explaining the structure–property of a molecule concerning the NLO characters, the concepts of polarizability and hyperpolarizability are helpful. 63 In addition to the NLO response, the properties of organic compounds offer a crucial role in the internal charge-transfer process and extended π-conjugated systems. 64 …”
Section: Resultsmentioning
confidence: 99%
“…All voltammograms show three redox processes corresponding to one irreversible reduction peak (implicating the acceptor end) and two reversible oxidation steps, related to the two one-electron oxidations of the pyranylidene unit, as previously described for other chromophores with a similar design 13b and D−π–A platinum complexes with this donor end. 21 …”
Section: Resultsmentioning
confidence: 99%
“…Gauthier et al reported a series of linear mono-and di-platinum complexes end-capped with diphenylpyranylidene (donor) and pentafluorophenyl (acceptor) moieties, including 45 which gave a low second-order NLO response in chloroform solution. 142 The length of the oligoyne linkers, and the number of platinum centres, did not significantly affect the NLO responses of these complexes. Their structural configuration plays a significant role, as a related V-shaped complex exhibited an NLO response twice as high as that of the linear counterpart.…”
Section: Nonlinear Optical (Nlo) Propertiesmentioning
confidence: 90%